2015
DOI: 10.1089/met.2014.0135
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Resistance Training Attenuates Acute Exertion-Induced Reductions in Arterial Function but Not Inflammation in Obese Women

Abstract: Background: Cardiovascular disease (CVD) is a leading cause of preventable death among young women in the United States. Habitual resistance exercise training is known to have beneficial effects on endothelial function and CVD risk factors, including obesity; however, previous studies show that acute resistance exercise impairs endothelial function in obese adults who are sedentary, a response that may be linked to inflammation. We sought to determine if circuit-based resistance training (CRT) attenuates acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
4
39
0
1
Order By: Relevance
“…Our primary outcome measures exceed these minimum effect sizes. In addition, the findings of this study align with previous studies of similar size and using a similar study population from our lab [10,15,18]. Nonetheless, the relationship between regular exercise and various stressors shown to induce vasodilator dysfunction remains an area that needs further exploration, particularly in the microvasculature during obesity.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our primary outcome measures exceed these minimum effect sizes. In addition, the findings of this study align with previous studies of similar size and using a similar study population from our lab [10,15,18]. Nonetheless, the relationship between regular exercise and various stressors shown to induce vasodilator dysfunction remains an area that needs further exploration, particularly in the microvasculature during obesity.…”
Section: Discussionsupporting
confidence: 87%
“…Brachial FMD is a surrogate of conduit artery endothelial cell function that has been found to be related to coronary artery function and to predict cardiovascular events [5,6]. The magnitude and duration of dysfunction is dependent upon fitness level and age [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acute exercise bouts paradoxically increase the risk of cardiovascular events in sedentary individuals, in part through a transient increase in blood pressure and endothelial dysfunction (2,9,15). Extensive work characterizing subcutaneous adipose resistance arteries has been done in humans (22,24,40), demonstrating that endothelium-dependent vasodilation in these arteries correlates with clinical measures of peripheral vascular function (6), that high intraluminal pressure elicits endothelial dysfunction in these arteries (9,40), and that regular exercise may be protective against said endothelial dysfunction (16,40).…”
Section: New and Noteworthymentioning
confidence: 99%
“…However, in another study, Franklin et al [46] showed that acute physical stress induced by resistance exercise reduces FMD in sedentary obese women, suggesting that this response to acute physical exertion may be an important marker for CV risk prediction in this population.…”
Section: Impact Of Exercise Prescription On Arterial Functionmentioning
confidence: 99%